EVALUASI FAKTOR-FAKTOR TATA KELOLA DAN KOMPLEKSITAS KORPORASI TERHADAP AUDIT FEE - Rizka Diah Rahmawati; Natrion; Heriston Sianturi; Tagor Darius Sidauruk (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2025)
The foundation of this research is aimed at examining the elements of corporate governance and the degree of organizational diversity in relation to audit fees among several companies in the agricultural and plantation sectors listed on the Indonesia Stock Exchange (IDX) during the period from 2019 to 2023. This quantitative study utilizes annual financial statements from firms in these sectors as secondary data. The analysis is conducted to explore the relationship and interaction between independent and dependent variables using multiple linear regression techniques